Onkologische Operationsberichte: Minimalanforderungen, rechtliche Aspekte und zukünftige Entwicklungen : Übersichten - Klose, Johannes; Böhm, Sandra; Bruns, Christiane; Chojecki, Paul; Conradi, Lena-Christin; Fichtner-Feigl, Stefan; Grützmann, Robert; Heberer, Jörg; Jansen-Winkeln, Boris; Jakob, Jens; Kohlhaw, Kay Rüdiger; Oehme, Astrid; et al. (Die Chirurgie, 2025)
The establishment of comprehensive oncological centers for the interdisciplinary care of cancer patients is based on defined criteria that must undergo regular external review to ensure a uniform quality standard of cancer care in Germany. The quality of surgical performance is defined, among other factors, by the number of cases treated or the experience of individual surgeons; however, the operation reports made are highly heterogeneous, as no specific requirements need to be met for certification as an oncological center. The German Association for Surgical Oncology (ACO) has therefore set the goal of proposing a minimum standard for oncological operation reports. In addition to the aspects to be included in the operation reports, exemplified with respect to individual organ systems, legal considerations and the use of artificial intelligence should also be examined in greater detail.